Metagenomic and metaproteomic analyses of microbial amino acid metabolism during Cantonese soy sauce fermentation - Chen, Cong; Wen, Lin Feng; Yang, Li Xin; Li, Jun; Kan, Qi Xin; Xu, Ting; Liu, Zhan; Fu, Jiang Yan; Cao, Yong (Frontiers in Nutrition, 2023)
Cantonese soy sauce is an important type of traditional Chinese brewed soy sauce that was developed in southern China, mainly in Guangdong. Due to the long fermentation period and complex microbiota in Cantonese soy sauce, there are few reports on the microbial metaproteomics of Cantonese soy sauce. In this study, integrative metagenomic and metaproteomic analyses were used to identify the changes in the dominant microbiota and amino acid synthesis-related enzymes and metabolism during Cantonese soy sauce fermentation. Metagenomic analysis revealed that Tetragenococcus halophilus, Weissella confusa, Weissella paramesenteroides, Enterobacter hormaechei, and Aspergillus oryzae were the dominant microbiota. Using the Top 15 dominant microbiota identified by metagenomics as the database, LTQ Orbitrap Velos Pro ETD mass spectrometry was used to obtain metaproteomic information about the microbes in the soy sauce, and the results indicated that the active enzymes involved in the metabolism of amino acids were secreted by microorganisms such as A. oryzae, T. halophilus, and Zygosaccharomyces rouxii. during the Cantonese soy sauce fermentation process. Among them, early fermentation (0-15d) was dominated by A. oryzae and T. halophilus , mid-term fermentation (60-90d) was dominated by Z. rouxii, A. oryzae, and T. halophilus ,and late fermentation (90-120d) was dominated by A. oryzae, Z. rouxii, and T. halophilus . Kyoto Encyclopedia of Genes and Genomes analysis revealed that the main enzymes involved in the metabolism of umami amino acids were aspartate aminotransferase, citrate synthase, aconitase, and isocitrate dehydrogenase , which were produced by Z. rouxii and A. oryzae during early fermentation (0-15 d) and the middle fermentation stage (60-90 d). This study constructed a regulatory network of enzymes potentially involved in the metabolism of flavour amino acids, which provided a theoretical basis for studying the amino acid metabolism of Cantonese soy sauce.